Inside Front Cover: pyFOOMB: Python framework for object oriented modeling of bioprocesses - Hemmerich, Johannes (Eng Life Sci, 2021)
DOI: 10.1002/elsc.202000088 The cover illustrates the close integration of experimental work and in silico analyses to study and optimize bioprocesses. In pages 242–257 of this issue, Hemmerich et al. introduce the tool pyFOOMB that enables a guided and flexible implementation of bioprocess models in the form of ordinary differential equation systems (ODEs). By building on Python as powerful and multi‐purpose programming language, ODEs can be formulated in an object‐oriented manner, which facilitates their modular design, reusability and extensibility. Moreover, in combination with Jupyter notebooks the education in bioprocess engineering and the applied learning of Python as scientific programming language is supported. The cover image was designed by Verena Resch (http://luminous-lab.com/). For details see article DOI 10.1002/elsc.202000088 on page 242. [Image: see text]